HUMAN RESOURCES MANAGEMENT OF HEALTHCARE INSTITUTIONS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Significant changes in the functioning of the health care sector determined the transition to a new management system, which is reflected in the management of health care facilities in general and in the management of human resources in particular. The modern development of high technologies leads to the transformation of work and the structure and quality of human resources. The requirements for the professional and qualification level of employees, work discipline, experience, individual characteristics and soft skills, the ability to master new knowledge and acquire new skills are increasing. Therefore, the role and place of a person in the organization is growing and there is a need to change approaches to human resource management.The purpose of the article: substantiation of the theoretical and methodological provisions of human resource management of health care institutionsResults. Based on the generalization of domestic and foreign works, the definition of human resources of the organization as a determining factor and the driving force of its development, which combines personal, business, professional qualities, the totality of which, with their continuous development, ensures strategic competitive advantages of the organization, has been clarified. The author's vision of the grouping of requirements for employees of health care institutions based on the competence approach, which takes into account such groups of criteria as basic (the same for all employees within a certain category), professional and general competencies (which can differ significantly even within the same category of employees) is substantiated ). The essence of human resources management as a set of methods, approaches, technologies for creating the necessary conditions and motivation of the organization's employees for the formation, development and realization of personal, business, and professional potential for achieving the goals of the organization, ensuring its competitiveness on the one hand, and the interests of employees on the other is specified. The methodological basis of human resources management has been improved based on the symbiosis of elements of basic concepts and models that determine the fundamental principles, criteria and approaches that take into account modern changes in the environment of organizations, the nature of work, requirements for employees and their positioning as a subject of the management process. The methodological aspects of human resources management have been developed, namely, criteria (competitiveness of human resources, human potential, efficiency of its use, optimal staffing), approaches (complex , institutional, structural-functional, functional, systemic, synergistic), which maximally take into account the specifics of the functioning of organizations. A conceptual model of human resources management has been developed, the main difference of which is the orientation to the person in all its manifestations and the creation of conditions for the development and realization of the personal, business, and professional potential of employees to achieve their own goals and the goals of the organization's development, ensuring its competitiveness.Conclusions. Human resources of the organization are the driving force of its development. They include personal, business, professional qualities. Human resources management consists in creating the necessary conditions and motivating the organization's employees to form, develop, and realize their personal, business, and professional potential to achieve the organization's goals, ensure its competitiveness on the one hand, and the interests of employees on the other.
Keywords: human resources, human resources management, healthcare institutions, competence approach, competitiveness of human resources, human potential.